WORKSHOP PEMBELAJARAN VOKAL BERBASIS PLATFORM MUSIK DIGITAL PADA KOMUNITAS BELAJAR MGMP SENI BUDAYA SMA KOTA PADANG - Esy Maestro; Alrizka Hairi Dilfa; Hermi Zaswita (COMMUNITY SERVICE JOURNAL OF ECONOMICS EDUCATION, 2025)
Vocal learning within the MGMP Seni Budaya SMA Kota Padang Learning Community faces significant challenges, particularly due to the limited availability of a harmonious musical instrument (keyboard) to accompany vocal exercises. Based on the data, only three keyboard units are available for all students in the vocal class, which is highly inadequate. Additionally, most students and teachers have not yet utilized digital music technology in the learning process. This community service activity aims to address these issues by providing intensive training on using the Musicca digital music platform as a flexible and independent alternative for vocal accompaniment. The methods used include socialization, practical training, technology implementation through Musicca-based vocal projects, as well as mentoring and evaluation. The expected outcomes are a measurable improvement in students' vocal skills through a digital project (targeting 80% of students showing better abilities) and the mastery of relevant digital music technology (targeting 85% of students mastering Musicca independently). The implementation of this digital platform also contributes to supporting the Merdeka Belajar Kampus Merdeka (MBKM) program and Main Performance Indicators (IKU) through technology-based learning experiences outside of the campus. Keywords:  Vocal Learning, Digital Music Platform, Learning Community, Arts and Culture